Stock Market Price Forecasting by Using Deep Learning - Reddy, Madhusudan; Gade, Arun; ., Sreekarreddy; Prabhu, P (International Journal of Engineering and Technology, 2018)
Stock market forecasts are an attempt to determine the future value of corporate capital or other financial products consumed in the stock market. If the future stock price forecast succeeds, you can gain great profit. The efficient market presents all the current stock price information, which shows that price fluctuations are not the basis for unnecessary new information. Others disagree that people who have these ideas have many methods and techniques to help them get future information. [1]